Associations of Bone Turnover Markers with Cognitive Function in Patients Undergoing Hemodialysis. (24th April 2020) - Wu, Ping-Hsun; Lin, Yi-Ting; Chen, Cheng-Sheng; Chiu, Yi-Wen; Tsai, Jer-Chia; Kuo, Po-Lin; Hsu, Ya-Ling; Ljunggren, Östen; Fellström, Bengt; Kuo, Mei-Chuan
Abstract : Background . Patients undergoing hemodialysis experience a greater risk of cognitive impairment than the general population, but limited data elucidates the biomarkers on this. We evaluated the association of bone turnover markers on cognitive function among 251 prevalent hemodialysis enrollees in a cross-sectional study. Methods . 251 hemodialysis patients (median age = 57.8, 55% men) and 37 control subjects (mean age = 61.2, 56% men) without a prior stroke or dementia diagnosis were enrolled. Serum concentrations of 8 bone markers were analyzed as the association of cognitive function (Montreal Cognitive Assessment (MoCA) and Cognitive Abilities Screening Instrument (CASI)) using linear regression analysis. Results . A lower cognitive function was noted in hemodialysis patients compared to control subjects. The receptor activator of nuclear factor kappa-B ligand (RANKL) was the only bone marker found to be associated with cognitive function (MoCA and CASI tests) in hemodialysis patients without a prior stroke or dementia diagnosis. In stepwise multiple linear regression analysis, the association remained significant in MoCA (β = 1.14, 95% CI 0.17 to 2.11) and CASI (β = 3.06, 95% CI 0.24 to 5.88). Short-term memory (β = 0.52, 95% CI 0.01 to 1.02), mental manipulation (β = 0.51, 95% CI 0.05 to 0.96), and abstract thinking (β = 0.57, 95% CI 0.06 to 1.09) were the significant subdomains in the CASI score related to RANKL. Conclusions . Serum RANKL levels were potentially associated with better cognitive function in hemodialysis patients. Further large-scale and prospective studies are needed to confirm our findings.